Economic value of knowing BRCA status: BRCA testing for prostate cancer prevention and optimal treatment. (16th March 2023) - Oh, Mok; McBride, Ali; Bhattacharjee, Sandipan; Slack, Marion; Jeter, Joanne; Abraham, Ivo
ABSTRACT: Background: We aimed to estimate the incremental lifetime effects, costs, and net-monetary-benefit (NMB) of knowing BRCA information by testing of patients with low-risk localized prostate cancer (PCa) in the US and guiding subsequent screening and treatment, and the cumulative savings or losses of yearly cohort testing over 16 years. We compared two strategies: (1)'with BRCA information' and (2)'without BRCA information.' We also estimated the expected value of perfect information. Methods: The incremental NMB (INMB) quantified the monetized benefit per person of knowing BRCA status. The net-monetized-value of knowing BRCA information was estimated by multiplying the INMB with the eligible population. Results: The INMBs of knowing BRCA information were 43, 357 (payer) and 43, 487 (society). in payer and societal perspectives, respectively. Escalated to the eligible patients in 2020, knowing BRCA status resulted in net monetized lifetime value of 1.7 billion (payer and society) for the 2020 cohort; and yielded accumulated net-monetized-value of 28.0 billion (payer) and 28.1 billion (society) over 16 yearly cohorts of eligible PCa patients. Conclusions: The economic value of knowing BRCA status for all low-risk localized PCa patients in the US provides short-term and long-term evidence for BRCA testing to screen early and optimize treatment.